2010
DOI: 10.1152/ajpendo.00179.2010
|View full text |Cite
|
Sign up to set email alerts
|

Roles for miRNA-378/378* in adipocyte gene expression and lipogenesis

Abstract: In this study, we explored the roles of microRNAs in adipocyte differentiation and metabolism. We first knocked down Argonaute2 (Ago2), a key enzyme in the processing of micro-RNAs (miRNAs), to investigate a potential role for miRNAs in adipocyte differentiation and/or metabolism. Although we did not observe dramatic differences in adipogenesis between Ago2 knock-down and control 3T3-L1 cells, incorporation of [(14)C]glucose or acetate into triacylglycerol, and steady-state levels of triacyglycerol were all re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(200 citation statements)
references
References 26 publications
8
188
1
3
Order By: Relevance
“…We found that mice lacking miR-378 and miR-378* are protected against diet-induced obesity. Previous studies have identified numerous metabolic regulatory proteins as targets for repression by miR-378 and miR-378* (10,(26)(27)(28). In addition, we found that carnitine O-acetyltransferase (CRAT), a mitochondrial enzyme involved in fatty acid metabolism (29,30), and MED13 are repressed by miR-378 and miR-378*, respectively.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…We found that mice lacking miR-378 and miR-378* are protected against diet-induced obesity. Previous studies have identified numerous metabolic regulatory proteins as targets for repression by miR-378 and miR-378* (10,(26)(27)(28). In addition, we found that carnitine O-acetyltransferase (CRAT), a mitochondrial enzyme involved in fatty acid metabolism (29,30), and MED13 are repressed by miR-378 and miR-378*, respectively.…”
mentioning
confidence: 65%
“…In addition, we noted a reduction of adipocyte size in mice lacking miR-378/378*, raising the possibility that these miRNAs are required for efficient hypertrophy and lipid uptake in white adipocytes. In this regard, overexpression of miR-378/378* in mesenchymal precursor cells has been shown to increase lipogenesis (26). The modulation of fatty acid metabolism by miR-378/378* is crucial not only in the context of adipogenesis, but also in the maintenance of cardiac function, given that the adult heart depends primarily on fatty acids as an energy source (47).…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al compared the expression of 89 bovine miRNAs in adipose tissues between three crossbreeds differing in backfat thickness, and found that 42 miRNAs were differentially expressed, of which miR-378 was most differentiated (Jin et al, 2010). miR-378 has been shown to play a role in lipogenesis in mice (Gerin et al, 2010). Thus, miR-378 might participate in the control of subcutaneous growth in cattle.…”
Section: Mirnas In Cattlementioning
confidence: 99%
“…As shown in Figure 4B, the induction of miR-24 and miR-34a by INZ(c) was abrogated by Ago2 knockdown, which is consistent with literature showing that knocking down RISC complex could affect the level of mature miRNAs. 31,32 Interestingly, Ago2 knockdown impaired the targeting of c-Myc by INZ(c) as shown in Figure 4C, suggesting INZ(c) regulates c-Myc expression via the miRNA pathway.…”
Section: Inz(c) Suppresses Growth Of Lymphoma Cellsmentioning
confidence: 84%